Step-Wise Decrease in Contact Line Velocity of Drops Impacting a Flat Smooth Surface - MATSUSHITA, Yohsuke; SAITO, Yasuhiro; SHIROTA, Minori; AOKI, Hideyuki; KODAMA, Ayaka; MATSUKAWA, Yoshiya; FUKUNO, Junichi; DAIKOKU, Masatoshi; MIYAGAWA, Taimei; SHIRAI, Keitaro; OKABE, Takahiro (JAPANESE JOURNAL OF MULTIPHASE FLOW, 2023)
Predicting the dynamics of impacting drops is crucial in various industrial applications such as spray and inkjet technologies. Especially in painting technology, the entrapment of air bubbles greatly reduces the product quality. The formation of a thin air film in front of the moving contact line causes the entrapment of air bubbles in the spreading phase. To clarify the main forces acting at the gas-liquid interface that induce air bubbles entrapment, we investigate the contact line velocity of impacting drops by taking bottom view images using the total internal reflection (TIR) method. We used droplets of glycerol or glycerol-ethanol solutions and solid surfaces covered with either glycerol or silicone oil. Our results show the contact line velocity decreased rapidly at Tc when a thin air film was formed and settled down at a constant value Vconst after the formation of the air film. Furthermore, we revealed that drop viscosity affects Tc and Vconst. Moreover, we found that after Tc, the lubrication pressure of the air had the same order of magnitude as the viscous shear stress of the drop, which implied the importance of the air lubrication pressure.